2008
DOI: 10.1152/ajpendo.00670.2007
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic pathways linking energy balance and reproduction

Abstract: During periods of metabolic stress, animals must channel energy toward survival and away from processes such as reproduction. The reproductive axis, therefore, has the capacity to respond to changing levels of metabolic cues. The cellular and molecular mechanisms that link energy balance and reproduction, as well as the brain sites mediating this function, are still not well understood. This review focuses on the best characterized of the adiposity signals: leptin and insulin. We examine their reproductive rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
220
1
13

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(238 citation statements)
references
References 109 publications
4
220
1
13
Order By: Relevance
“…Among those, it is well known that puberty onset and fertility are sensitive to the magnitude of body fuel (energy) reserves and under the regulation of key appetite-controlling factors, such as leptin (FernandezFernandez et al 2006, Hill et al 2008. Our recent data strongly suggest that central nesfatin-1 signaling might be involved as well in the regulation of the timing of puberty in the female rat.…”
Section: Nesfatin-1 and The Neuroendocrine Control Of The Reproductivmentioning
confidence: 55%
See 1 more Smart Citation
“…Among those, it is well known that puberty onset and fertility are sensitive to the magnitude of body fuel (energy) reserves and under the regulation of key appetite-controlling factors, such as leptin (FernandezFernandez et al 2006, Hill et al 2008. Our recent data strongly suggest that central nesfatin-1 signaling might be involved as well in the regulation of the timing of puberty in the female rat.…”
Section: Nesfatin-1 and The Neuroendocrine Control Of The Reproductivmentioning
confidence: 55%
“…Compelling experimental evidence has demonstrated that central pathways and peripheral signals responsible for body weight homeostasis commonly participate also in the control of related functions, which are gated by the metabolic state of the organism (Fernandez-Fernandez et al 2006, Hill et al 2008. Among those, it is well known that puberty onset and fertility are sensitive to the magnitude of body fuel (energy) reserves and under the regulation of key appetite-controlling factors, such as leptin (FernandezFernandez et al 2006, Hill et al 2008.…”
Section: Nesfatin-1 and The Neuroendocrine Control Of The Reproductivmentioning
confidence: 99%
“…Like its near neighbor, the infundibular nucleus (also termed the arcuate nucleus of the hypothalamus), damage to the ventromedial nucleus of the hypothalamus has been linked to obesity syndromes in humans (Bray and Gallagher, 1975;Carmel, 1980;Lustig, 2002;Swaab, 2006). The infundibular nucleus plays a key role in relaying peripheral information to the metabolic and the reproductive brain (Dudas and Merchenthaler, 2006;Morton et al, 2006;Hill et al, 2008;Simpson et al, 2009). The ventromedial hypothalamus, which comprises both the ventromedial nucleus of the hypothalamus and the infundibular nucleus, might be an interesting site to target for body weight control in morbidly obese patients (Halpern et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It participates in the interpretation of olfactory/vomeronasal information and remarkable projections leave this subnucleus via the ST to reach the hypothalamic ventromedial nucleus, the anteroventral periventricular nucleus, the preoptic area, and the ventral premammillary nucleus in the hypothalamus (Newman, 1999;Dong et al, 2001;Petrovich et al, 2001). These hypothalamic nuclei considerably affect food intake and energy balance (Hill et al, 2008). The MePD also projects to the subiculum, which would be involved in prioritizing the temporal organization of motivated behaviors .…”
mentioning
confidence: 99%